2023
DOI: 10.1002/ccr3.7275
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of junctional epidermolysis bullosa, autosomal recessive deafness type 57, and Angelman syndrome: A case report

Abstract: The presence of more than one genetic/genomic disorder is not uncommon. It is therefore essential to continuously consider new signs and symptoms over time. Administration of gene therapy could be extremely difficult in particular situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Another case report described developmental delay, and hearing loss in a patient with 3M syndrome due to co-existence variants in CUL7 and ILDR1 gene ( 16 ). Also, Amato et al reported a case of Angelman syndrome (5,5 Mb deletion of 15q11.2–q13.1) with a coexisting intermediate junctional epidermolysis bullosa (COL17A1, c.3766 + 1G > A, homozygous) and autosomal recessive deafness type 57 (PDZD7, c.883C > T, homozygous) ( 17 ). This “double trouble” case illustrates the point that clinical findings in patients might not be explained by a single genetic defect, and consanguineous marriage increases the likelihood of coexistence of autosomal recessive diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another case report described developmental delay, and hearing loss in a patient with 3M syndrome due to co-existence variants in CUL7 and ILDR1 gene ( 16 ). Also, Amato et al reported a case of Angelman syndrome (5,5 Mb deletion of 15q11.2–q13.1) with a coexisting intermediate junctional epidermolysis bullosa (COL17A1, c.3766 + 1G > A, homozygous) and autosomal recessive deafness type 57 (PDZD7, c.883C > T, homozygous) ( 17 ). This “double trouble” case illustrates the point that clinical findings in patients might not be explained by a single genetic defect, and consanguineous marriage increases the likelihood of coexistence of autosomal recessive diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Mb deletion of 15q11.2-q13.1) with a coexisting intermediate junctional epidermolysis bullosa (COL17A1, c.3766 + 1G > A, homozygous) and autosomal recessive deafness type 57 (PDZD7, c.883C > T, homozygous)(17). This "double trouble" case illustrates the point that clinical findings in patients might not be explained by a single genetic defect, and consanguineous marriage increases the likelihood of coexistence of autosomal recessive diseases.…”
mentioning
confidence: 85%